Generative AI as a Live Design Mentor: A Mixed-Reality Approach to Graphic Design Education - Solikhan, Muhammad; Priyadi, Agus; MacDonald, Don; Noramai, Avee (International Journal of Graphic Design, 2026)
The transformation of graphic design education in the post-pandemic era has introduced new challenges in fostering meaningful visual interactions between students and AI-based technologies. This context calls for design approaches that are not only technically adaptive but also conceptually reflective. This study aims to explore and develop a visual approach to capture the creative engagement of design students in hybrid learning environments, specifically through prompt-based experimentation with AI-generated visuals. The research adopts a Design-Based Research (DBR) methodology in a single-case study, involving iterative cycles of visual design, reflection, and evaluation. Data were collected through observation, design documentation, and narrative analysis of visual outputs. The findings reveal that AI prompt interventions encouraged a reinterpretation of the creative process, highlighting students' roles as active interpreters in shaping meaningful visuals. The project outcomes include a series of digital experimental visuals that symbolically and contextually represent human–AI interaction. This study concludes that designers must be positioned as meaning-makers within AI-assisted visual systems, and it opens possibilities for more inclusive and participatory design practices in the future. The implication is that graphic design can serve as a critical bridge between technology, human values, and ethical visual communication within the evolving landscape of digital learning.